Mikrotik Optimization and Pc Cloning on Computer Networks with Using UBIQU Satellite Internet Vsat Broadband - S Sumarlin; Muhammad Zarlis; S Suherman; Syahril Efendi (LPPM STIKOM Tunas Bangsa, 2022)
The internet is currently growing rapidly. The need and rapid development in the use of the Internet network requires a balance in the provision of Internet facilities. Internet standard services are the continuity of the connectivity of the Internet. Connections from the Internet are required to always be awake under any conditions, but not always connectivity will run smoothly, many obstacles or disturbances are encountered so that the connection does not run smoothly. One effective method that can be done is to apply the PCQ method in dividing the amount of internet bandwidth by paying attention to the distribution pattern of bandwidth speed based on the number of active users at a certain time. The subjects taken in this study were users who were active during the active period of students and other users in the Hotspot network at the Indonesian Institute of Technology and Business. The method used is a case study method based on the level of activity of the hotspot network on campus. Comparison between the amount of bandwidth for the number of users between the hours of high activity in the morning until the afternoon, and the hours of low activity in the afternoon until the evening. The PCQ method will divide the bandwidth based on the number of active users on the hotspot with the same amount. The design is continued by applying the PCQ method using Miktrotik Routerboard, testing is carried out by technical testing by testing the amount of bandwidth with division based on the number of active users and the same results are obtained.